2021
DOI: 10.1002/fes3.295
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen/potassium interactions increase rice yield by improving canopy performance

Abstract: Rice (Oryza sativa L.) is one of the most vital staple foods in the world and provides food for more than 3.5 billion people (Godfray et al., 2010). It is estimated that global rice production needs to increase by 116 Tg by 2035 to meet the expected population increase (Yamano et al., 2016). Therefore, increasing rice production is crucial to ensuring world food security. Many strategies to improve rice yield have been investigated, such as breeding of super-hybrid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Field trial‐based European studies have also found that integrating fertilisation with organic amendment applications led to consistently higher agronomic performance than crops treated with only one or the other (Macholdt et al, 2019; Sihvonen et al, 2021). This approach has also been applied to farming systems in the developing world (Abid et al, 2020; Qazi & Khan, 2020), particularly in the cultivation of rice in which substantial improvements to crop performance and quality have been obtained through combining synthetic N additions with K inputs (Ye et al, 2021), retention and reincorporation of residues (Tang et al, 2021). An important next step is to connect findings from the efficiency index to soil quality.…”
Section: Discussionmentioning
confidence: 99%
“…Field trial‐based European studies have also found that integrating fertilisation with organic amendment applications led to consistently higher agronomic performance than crops treated with only one or the other (Macholdt et al, 2019; Sihvonen et al, 2021). This approach has also been applied to farming systems in the developing world (Abid et al, 2020; Qazi & Khan, 2020), particularly in the cultivation of rice in which substantial improvements to crop performance and quality have been obtained through combining synthetic N additions with K inputs (Ye et al, 2021), retention and reincorporation of residues (Tang et al, 2021). An important next step is to connect findings from the efficiency index to soil quality.…”
Section: Discussionmentioning
confidence: 99%
“…Since rice is a sensitive crop (Ma et al, 2015; Reddy et al, 2021), global climate change has caused various injuries to rice crops due to fluctuating temperature, ultimately reducing rice yield (Dar et al, 2021; Pandit et al, 2017; Pradhan et al, 2019). Hence, new approaches are required to increase rice production in regions vulnerable to climate change for ensuring global food security (Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%